2012
DOI: 10.1038/gim.2012.18
|View full text |Cite
|
Sign up to set email alerts
|

Performance of PREMM1,2,6, MMRpredict, and MMRpro in detecting Lynch syndrome among endometrial cancer cases

Abstract: Purpose Lynch syndrome accounts for 2–5% of endometrial cancer cases. Lynch syndrome prediction models have not been evaluated among endometrial cancer cases. Methods Area under the receiver operating curve (AUC), sensitivity and specificity of PREMM1,2,6, MMRpredict, and MMRpro scores were assessed among 563 population-based and 129 clinic-based endometrial cancer cases. Results A total of 14 (3%) population-based and 80 (62%) clinic-based subjects had pathogenic mutations. PREMM1,2,6, MMRpredict, and MMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…Of them, four used population-based samples,74 82–84 10 used clinic-based samples,71 72 75 85–91 and three used both clinic-based and population-based samples 73 92 93. Given there was significant evidence of heterogeneity between studies, we reported the pooled AUC values from random effect models (detail in table 2).…”
Section: Prediction Modelsmentioning
confidence: 99%
“…Of them, four used population-based samples,74 82–84 10 used clinic-based samples,71 72 75 85–91 and three used both clinic-based and population-based samples 73 92 93. Given there was significant evidence of heterogeneity between studies, we reported the pooled AUC values from random effect models (detail in table 2).…”
Section: Prediction Modelsmentioning
confidence: 99%
“…These models were validated in the colorectal cancer population for the detection of MLH1 , MSH2 , and MSH6 mutations with favorable results. When applied to the endometrial cancer patient population, however, these models fail to perform at a level that would support their use as a clinical screening tool (8). …”
Section: Introductionmentioning
confidence: 99%
“…Risk prediction models, such as MMRpredict,15 PREMM,16 MMRPro17 and MsPath,18 calculate an individual's risk of Lynch syndrome, predominantly using a combination of family history, the patient's age at diagnosis, and the site of the colorectal tumour. There is no agreement, however, on the risk threshold meriting formal screening for Lynch syndrome.…”
Section: Discussionmentioning
confidence: 99%